The Role of Gadgets in Building Intelligent Students with Pancasila Character in the Digital Era - M. Iham Pratama; Cahyo Hasanudin; Ernia Duwi Saputri (International Forum of Researchers and Lecturers, 2025)
The digital era is characterized by the widespread use of gadgets in daily life. In this era, gadgets also play a crucial role in building Pancasila character. This study explores the role of gadgets in shaping Pancasila character in students, focusing on both the positive and negative impacts and the opportunities available. Using the Systematic Literature Review (SLR) method, the study draws on secondary data from various national journals. Data collection was conducted through observation and note-taking, with validation using triangulation. The findings reveal that gadgets significantly contribute to shaping intelligent students who embody Pancasila values in the digital era. The study identifies four key roles of gadgets: 1) providing access to information and knowledge, 2) fostering collaboration and communication, 3) supporting the development of digital skills, and 4) promoting the formation of Pancasila character. The study concludes that gadgets are instrumental in enhancing students' learning and character development in the digital age.